Solving a class of quadratic matrix equations. (August 2018) - Adam, Mansour Saeed Ibrahim; Ding, Jiu; Huang, Qianglian; Zhu, Lanping
Abstract: Let A be a matrix with A − 1 = A . We find all commuting solutions and some non-commuting solutions of the matrix equation A X A = X A X . All non-commuting solutions are also obtained under a full rank condition.